Pendidikan Inklusif pada Mata Pelajaran Bahasa Jawa di SMP Negeri 31 Semarang - Anggeani, Tia Yulian; Utami, Esti Sudi (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2023)
Education in Indonesia in general still separates a children with special needs and normal children. This situation can creates discrimination against the children with special needs. As an alternative, the government determines the implementation of inclusive education in the Regulation Minister of National Educational Number 70 Year 2009. The learning's implementation in inclusive schools has several differences with regular schools. The proper learning will make it easier for ABK to take part in learning process. In addition, there are also several factors that support the implementation of inclusive education. Inclusive schools should pay attention to these factors. The objectives of this study were to describe the learning process for the children with special needs in an inclusive education setting on Javanese language in SMP Negeri 31 Semarang and to describe the factors supporting and inhibiting the implementation of inclusive education. This research is an evaluation research using qualitative research methods, data were collected using interview techniques. The results showed that the implementation of inclusive education at SMP Negeri 31 Semarang has not been effective. This is evidenced by the relatively lower values obtained by ABK compared to the normal children. Another thing is also evidenced from the lesson plan which does not begin with an assessment process, but with a process of detection and compiling of PPI. However, the teaching system, learning models, learning methods, instructional media, and learning aspects have been running according to the theory of experts.